Analysis of The Management of Early Breastfeeding Initiation in The Era of New Habits from The Mother's Side - Trianingsih, Indah; Marlina, Marlina; Wastiani, Ima; Sari, Adinda Juwita (Poltekkes Kemenkes Palu, 2024)
Introduction: Early breastfeeding initiation is vital for newborn health, particularly during the COVID-19 pandemic, which has necessitated new health protocols. This study examines the management of early breastfeeding initiation from the mother's perspective, focusing on their knowledge and attitudes toward adherence to COVID-19 safety measures. Methods: A cross-sectional quantitative study was conducted with 109 mothers giving birth at midwives' independent practices in Bandar Lampung in 2023, using purposive sampling. Data were collected on maternal knowledge, attitudes, and compliance with COVID-19 protocols during early breastfeeding. Frequency distribution and Spearman Rank's Correlation were used for data analysis. Results: Out of 102 respondents, 91.7% demonstrated good knowledge about early breastfeeding initiation, and 90.8% had a positive attitude towards its management. Compliance with COVID-19 protocols was observed in 64.2% of the participants. The Spearman Rank’s Correlation analysis showed a p-value of 0.000, indicating a significant relationship between maternal knowledge and attitudes and the management of early breastfeeding. Conclusion:The findings suggest that better knowledge and positive attitudes among mothers are associated with greater adherence to COVID-19 protocols in early breastfeeding initiation. These factors are crucial for effective breastfeeding practices during the pandemic.